Scientific selling creating high-performance sales teams through applied psychology and testing - Martini, Nancy, 1959-; James, Geoffrey, 1953-; ProQuest (Firm) (Hoboken, N.J. : Wiley, 2012)
"A truly scientific approach to measuring and improving sales performanceScientific Selling shows how statistically-valid measurement can improve every element of the sales environment&emdash;from management to coaching to training to creating long-term sustainable sales results. Sales organizations that embrace applied psychology and testing become more competitive because they don't waste resources on irrelevant or counterproductive activities. Managers can better assess the reasons behind individual and group performance and predictably improve sales results, while fostering a sales culture that attracts and retains personnel who have the personality and motivation to be successful.Scientific Selling includes more than a dozen specific stories demonstrating how scientific measurement improved overall sales performance through easily understood graphics, charts, and descriptions. It details how those teams were measured and how those metrics changed as the result of better hiring practices and better targeted coaching and sales training. Through these detailed case studies, Scientific Selling illustrates the importance of measurement for steering the success of your company. The book: Describes how the Clark-Mortenson Agency used scientifically proven data-based assessment tools to provide individual sales professionals with a very specific overview to determine their current strengths and areas of growth Examines Meadowbrook Golf's program to "manage for individual success" by using scientific testing and measurement to help its top managers understand what motivated their employees Details how Yankee Candle used scientific measurement to identify the right people to hire, and then used customer case studies and role-playing to focus on leveraging each individual's natural behavior to sell, thereby creating increases of 40% in sales revenue for trained individuals Scientific testing and measurement can leverage current strengths, identify areas for growth, and increase revenue. Chart your company's course through the power of Scientific Selling"--
Machine generated contents note: DEDICATION 6 ACKNOWLEDGEMENTS 7 PREFACE 11 FOREWORD 17 CHAPTER 1: THE SCIENCE of SELLING 20 The Changing Nature of Selling 21 The Crisis in Sales Management 24 The Advent of Scientific Selling 29 CHAPTER 2: The SCIENCE of BEHAVIORAL ASSESSMENT 33 Behavioral Assessment 33 Behavioral Surveys 36 Business Applications of Behavioral Science 37 The Effectiveness of Behavioral Assessment 40 How to Choose a Behavioral Assessment Method 41 CHAPTER 3: The SCIENCE of SALES SKILLS ASSESSMENT 46 The History of Sales Skill Assessment 47 The Advent of Sales Process 48 The Limitations of Sales Process 49 Evolution of Sales Skills 51 Limitations of "Solution Selling" 52 The Selling Skills Assessment Tool (SSAT) 53 CHAPTER 4: THE SCIENCE of HIRING SALES TALENT 57 How Most Companies Hire (and Why It Fails) 59 The Scientific Approach to Hiring 61 How to Implement Scientific Hiring 62 STEP #1: Analyze the Job. 63 STEP #2: Design an Appropriate Recruitment Ad 64 STEP #3: Filter the Resumes 65 STEP #4: Conduct Telephone Interviews 66 STEP #5: Give the Candidates a Behavior Assessment 67 STEP #6: Conduct Strategic Interviews 68 STEP #7: Refine the Model 69 Case Study: Rainsoft 69 Case Study: Centier Bank 71 CHAPTER 5: THE SCIENCE of SALES TRAINING 73 Why Sales Training Fails 74 Why Sales Training Doesn't Get Measured 76 Scientific Measurement vs. Conventional Wisdom 78 Applying Science to Sales Training 80 Customizing Sales Training 84 Case Study: The Clark-Mortenson Agency 85 Case Study: Yankee Candle 87 CHAPTER 6: THE SCIENCE of SALES COACHING 89 Sales Coaching and Behavioral Assessment 89 Sales Coaching and Skills Assessment 93 The Muscle Scenario 94 The Execution Scenario 95 The Knowledge Scenario 95 The Leverage Scenario 96 Example of Scientific Coaching 96 Cross-Cultural Aspects of Sales Coaching 98 Case Study: First Nonprofit Insurance 100 Case Study: LexisNexis 101 CHAPTER 7: THE SCIENCE of SALES MANAGEMENT 105 Reducing Sales Personnel Turnover 106 The Right Job for the Right Person 108 The Importance of an Upward Career Path 109 Effective Use of Sales Technology 110 Building a Culture of Innovation and Entrepreneurship 112 What is Creative Leadership? 112 How to Implement Creative Leadership 114 Fostering Entrepreneurship 116 The Importance of Non-Entrepreneurial Creativity 119 Using Science to Manage Change 120 Case Study: Bell Mobility Canada 123 Case Study: Meadowbrook Gold 126 CHAPTER 8: THE SCIENCE of SALES PROCESS 128 Customer Focused Selling 128 Process Stage #1: Applying the "Open" Skill 130 Process Stage #2: Applying the "Investigate" Skill 134 Process Stage #3: Applying the "Present" Skill 137 Process Stage #4: Use the "Confirm" Skill 139 Process Stage #5: Use the "Position" Skill 142 Case Study: Terminal Supply 144 Case Study: Blood Centers of America 146 CHAPTER 9: HOW SCIENTIFIC IS IT? 149 What Makes Assessments Scientific 150 The Predictive Index (PI) 151 The Objectivity of PI 153 The Reliability of PI 154 The Validity of PI 155 The Demographics of PI 156 The Sales Skill Assessment Tool (SSAT) 157 The Objectivity of SSAT 157 The Reliability of SSAT 158 The Validity of SSAT 158 The Demographics of SSAT 159 Studies of Behavioral Assessments 160 CHAPTER 10: THE FUTURE OF SCIENTIFIC SELLING 161 Cognitive Science 162 Human Analytics 163 Predictive Analytics 165 Neuroscience 166 A Final Word 168.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Selling -- Psychological aspects; Success in business; Electronic books